INDEKS INOVASI PENGELOLAAN KEUANGAN PADA DINAS KESEHATAN KABUPATEN SUMBAWA - I Nyoman Sutama; Nining Sudiyarti; Diah Fidayanti (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
The purpose of this study was to know the financial management innovation index at the Public Health Office (Dinas Kesehatan) of Sumbawa District. The type of this study was descriptive study. The data used in this study was primary data. The technique used to collect data was through questionnaire. The populations in this study were all employees at the Public Health Office (Dinas Kesehatan) of Sumbawa District. The technique of determining the sample was using the Slovin formula, therefore the number of samples in this study was 55 samples. The data analysis technique used was standard equation for calculating the innovation index. Based on the results of the data analysis, the value of each dimension were as follow: The dimension of novelty with innovation score was of 7.74, the dimension of productive with value was of 7.76, the dimension of impact with value was of 7.52 and dimension sustainable with value was of 7.55. Then from the results of all the dimension concluded that financial management innovation index at the Public Health Office (Dinas Kesehatan) of Sumbawa District was 76.3 or 76.30% with the "Innovative" category.